2018
DOI: 10.1093/mnras/sty2512
|View full text |Cite
|
Sign up to set email alerts
|

WASP-128b: a transiting brown dwarf in the dynamical-tide regime

Abstract: Massive companions in close orbits around G dwarfs are thought to undergo rapid orbital decay due to runaway tidal dissipation. We report here the discovery of WASP-128b, a brown dwarf discovered by the WASP survey transiting a G0V host on a 2.2 d orbit, where the measured stellar rotation rate places the companion in a regime where tidal interaction is dominated by dynamical tides. Under the assumption of dynamical equilibrium, we derive a value of the stellar tidal quality factor log Q = 6.96 ± 0.19. A combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The binary lightcurve software ellc was used to generate orbital and light curve models [22], and we employed the affineinvariant MCMC sampler emcee to explore parameter space [23]. We validated our approach [60,14] by re-analysing data from the eclipsing binary system WW Aurigae [61] and found a 1σ agreement with reported values.…”
Section: Global Analysis Of the Radial Velocity And Photometric Datamentioning
confidence: 80%
“…The binary lightcurve software ellc was used to generate orbital and light curve models [22], and we employed the affineinvariant MCMC sampler emcee to explore parameter space [23]. We validated our approach [60,14] by re-analysing data from the eclipsing binary system WW Aurigae [61] and found a 1σ agreement with reported values.…”
Section: Global Analysis Of the Radial Velocity And Photometric Datamentioning
confidence: 80%
“…TOI-503b has an intermediate-mass of 53.7 ± 1.2 M J , an inclination angle of 82.25 +0.31 −0.41 degrees (b = 0.974 +0.022 −0.015 ), and lies in the driest part of the brown dwarf desert (35-55 M J sin i, P ≤ 100 days, Ma & Ge (2014b)). There is a paucity of objects detected in this driest region of the brown dwarf desert, but in recent years, 5 BDs (Gillen et al (2017), Nowak et al (2017), Hodžić et al (2018), Carmichael et al (2019), Persson et al (2019), and this work) have been discovered in this intermediate mass-range, bringing new life, so to speak, to the desert and increasing the overall tally in the aforementioned range to 6. The recent growth in the discoveries of this type of BDs could be a hint at an undisclosed population in the driest part of the BD desert.…”
Section: The Transiting Bd Populationmentioning
confidence: 58%
“…Some binaries could be formed at the middle of the BDD, because of some scarce initial conditions. We need more similar systems, followed by in-depth studies, to understand the nature of these special cases (e.g., WASP-128b, Hodžić et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…cores (e.g., Kumar 1962Kumar , 1963Hayashi & Nakano 1963). In this view, the few detected brown-dwarf (BD) secondaries with short orbital periods (e.g., Bouchy et al 2011;Triaud et al 2017;Grieves et al 2017;dos Santos et al 2017;Beatty et al 2018;Hodžić et al 2018) are just oases found inside the 'desert'.…”
mentioning
confidence: 99%